Thinness, overweight, and obesity in 6‐ to 9‐year‐old children from 36 countries: The World Health Organization European Childhood Obesity Surveillance Initiative—COSI 2015–2017. (7th July 2021) - Spinelli, Angela; Buoncristiano, Marta; Nardone, Paola; Starc, Gregor; Hejgaard, Tatjana; Júlíusson, Petur Benedikt; Fismen, Anne‐Siri; Weghuber, Daniel; Musić Milanović, Sanja; García‐Solano, Marta; Rutter, Harry; Rakovac, Ivo; et al.
Summary: In 2015–2017, the fourth round of the World Health Organization (WHO) European Childhood Obesity Surveillance Initiative (COSI) was conducted in 36 countries. National representative samples of children aged 6–9 (203, 323) were measured by trained staff, with similar equipment and using a standardized protocol. This paper assesses the children's body weight status and compares the burden of childhood overweight, obesity, and thinness in Northern, Eastern, and Southern Europe and Central Asia. The results show great geographic variability in height, weight, and body mass index. On average, the children of Northern Europe were the tallest, those of Southern Europe the heaviest, and the children living in Central Asia the lightest and the shortest. Overall, 28.7% of boys and 26.5% of girls were overweight (including obesity) and 2.5% and 1.9%, respectively, were thin according to the WHO definitions. The prevalence of obesity varied from 1.8% of boys and 1.1% of girls in Tajikistan to 21.5% and 19.2%, respectively, in Cyprus, and tended to be higher for boys than for girls. Levels of thinness, stunting, and underweight were relatively low, except in Eastern Europe (for thinness) and in Central Asia. Despite the efforts to halt it, unhealthy weight status is still an important problem in the WHO European Region.